Measuring and monitoring gender equality : Malaysia 's gender gap index. (Kuala Lumpur: Ministry of Women, Family and Community Development, 2007)
Findings and insights of reducing gender inequalities in Malaysia
Keywords: Sex discrimination against women -- -- Malaysia; Sex role -- -- Malaysia; Women's rights -- -- Malaysia